1991
DOI: 10.5636/jgg.43.899
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Mid-Latitude Travelling Ionospheric Disturbances Associated with Mild Spread-F Conditions.

Abstract: Several diverging duplicate traces and one converging duplicate trace for mild mid-latitude spread-F events (on one particular night) have been used to investigate medium-scale travelling ionospheric disturbances (TIDs) during night hours. Sweptfrequency and fixed-frequency sonograms (which have phase information added) show spread-F characteristics similar to those recorded for more intense spread-F events. These include modulated height rises in the isoionic contours and electron-density depletions. The phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The F2-layer frontal structures (bands) reported by Behnke (1979) from a northern-hemisphere mid-latitude location are moving in south-west directions. As travel speeds and structure spacings are consistent with those reported by McNicol et al (1956) and Bowman (1960aBowman ( , 1991b, it is possible that these are moving spread-F structures. However Behnke suggests "that these bands are manifestations of the so-called 'Perkins' instability" (Perkins, 1973).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The F2-layer frontal structures (bands) reported by Behnke (1979) from a northern-hemisphere mid-latitude location are moving in south-west directions. As travel speeds and structure spacings are consistent with those reported by McNicol et al (1956) and Bowman (1960aBowman ( , 1991b, it is possible that these are moving spread-F structures. However Behnke suggests "that these bands are manifestations of the so-called 'Perkins' instability" (Perkins, 1973).…”
Section: Discussionsupporting
confidence: 84%
“…Evidence is now being found to suggest that the FAIs recorded at Es-layer levels by the MU-radar are associated with MS-TIDs (Woodman etal., 1991;Yamamoto etal.,1993Yamamoto etal., ,1994Tsunoda etal.,1994). TheE5-layer level FAIs recorded in Japan at 25 MHz, by Tanaka and Venkateswaran (1982) were found to be travelling in west to southwest directions with speeds comparable with those of nighttime F2-layer MS-TIDs (Bowman, 1991b).…”
Section: Some Characteristics Of Nighttime Medium-scale Travelling Iomentioning
confidence: 84%
See 1 more Smart Citation
“…The AU index [Allen and Kroehl, 1975, Figure 5] has a well-defined maximum near 1800 LT (these results are also given by Mayaud [1980]). Thus it is suggested that the negative association (illustrated in Figures 1 and 4 [Bowman, 1990[Bowman, , 1991b[Bowman, , 1991c. Figure 12 of Bowman [1990] illustrates these relationships where the foF2 reduction is about 1 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…On Fig. 1(b) three duplicate traces produced by tilted isoionic surfaces approximately 45 km apart (Bowman, 1991a) are clearly visible. The trace identified by the symbol B results from radiowaves reflected from an isoionic surface tilted about 43 degrees from the horizontal.…”
Section: Introductionmentioning
confidence: 98%